Cortisol and epinephrine alter the adipose functions and the mobilization of PCBs in adipose tissue slices from elephant seal - Pirard, Laura; Khudyakov, Jane I.; Crocker, Daniel E.; Van Hassel, Liesbeth; Scholl, Georges; Eppe, Gauthier; Page, Melissa M.; Rees, Jean-François; Smith, Donald R.; Debier, Cathy (Frontiers in Marine Science, 2023)
Marine mammals are exposed to increasing intensities of anthropogenic stressors such as acoustic disturbance and contaminants. Correlative studies have suggested concerning shifts in behavioral and physiological status of stress-exposed individuals, which could alter the health and survival of marine mammal populations. However, functional studies of the effects of multiple stressors on marine mammals are lacking. To fill in this gap, we recently developed an ex vivo approach of precision-cut adipose tissue slices (PCATS) to study the impact of stressors on the function of an essential endocrine organ: the adipose tissue. In the present study, we investigated the impact of hormones associated with the stress response on adipose tissue from northern elephant seals (Mirounga angustirostris). Blubber biopsies were collected from 18 weaned northern elephant seal pups, separated into inner and outer layers, dissected into PCATS, and cultured for 48 hours. To mimic prolonged and short-term exposure to physiological stress, PCATS were treated with 2 µM cortisol (CORT) for the entire 48 hours or 100 nM epinephrine (EPI) for the last 12 hours of culture, respectively. Hormones were applied individually or in combination. CORT and EPI exhibited an interacting, blubber layer-dependent, effect on adipose tissue biology, as quantified by gene expression in PCATS, and release of glycerol, free fatty acids, leptin and polychlorinated biphenyls into culture media. EPI stimulated a higher rate of lipolysis than CORT in PCATS from both blubber layers. The combination of CORT and EPI upregulated the expression of adipose triglyceride lipase in inner blubber PCATS and downregulated hormonesensitive lipase in outer blubber-derived PCATS. Expression of the leptin gene and secretion of the leptin adipokine were both decreased by EPI, while addition of CORT attenuated this effect in inner blubber PCATS only. CORT also increased the expression of the antioxidant enzyme glutathione peroxidase 3 in PCATS from both blubber layers. Polychlorinated biphenyls exhibited selective and limited mobilization from PCATS treated with stress hormones, highlighting the lipophilic properties of these toxic compounds. This study showed that physiological stress can impact several essential functions of marine mammal blubber, such as lipolysis and adipokine production.